Leptin promotes apoptosis and inhibits autophagy of chondrocytes through upregulating lysyl oxidase-like 3 during osteoarthritis pathogenesis. Issue 7 (July 2016) - Huang, Z.M.; Du, S.H.; Huang, L.G.; Li, J.H.; Xiao, L.; Tong, P.
Summary: Objective: Leptin has been found highly expressed in human osteoarthritis. We aimed to explore the possible effects and mechanisms of leptin on the apoptosis and autophagy of chondrocytes during osteoarthritis pathogenesis. Methods: Gene expression profile from osteoarthritis affected and preserved cartilage were downloaded from NCBI's Gene Expression Omnibus database (GSE57218 ). Lysyl oxidase-like 3 (LOXL3) mRNA expression in cartilage tissues and leptin concentration in joint synovial fluid (SF) was measured in samples from 45 osteoarthritis patients and 25 healthy donors by real-time PCR and radioimmunoassay, respectively. Rat osteoarthritis model was induced by anterior cruciate ligament transection (ACLT). The expression of apoptosis regulators and autophagy markers were detected by Western blot. Cell survival and cell apoptosis were identified by CCK-8 and flow cytometry, respectively. Results: Re-analysis onGSE57218 indicated that LOXL3 mRNA was upregulated in osteoarthritis affected cartilage. LOXL3 mRNA was upregulated in osteoarthritis patients, which was positively correlated with SF leptin concentration. Similar results were obtained in rat osteoarthritis model. Moreover, ACLT surgery led to a significant increase in the protein levels of cleaved caspase 3, and a notable decrease in the protein levels of Bcl-2, LC3 II/LC3 I and Beclin1. Silencing of LOXL3 in ACLT and leptin treated primary chondrocytes significantly inhibited cell apoptosis, and promoted cell proliferation and autophagy. Moreover, overexpression of LOXL3 remarkably inhibited autophagy of chondrocytes via activating mTORC1. Conclusions: LOXL3, a downstream of leptin, stimulated the apoptosis, but inhibited the autophagy of chondrocytes. LOXL3 is a potential therapy target for osteoarthritis.